2012
DOI: 10.2486/indhealth.ms1318
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on the Effects of a Combined Sleep Hygiene Education and Behavioral Approach Program on Sleep Quality in Workers with Insomnia

Abstract: To evaluate the effects of a combined sleep hygiene education and behavioral approach program on sleep quality in workers with insomnia, we conducted a randomized controlled trial at a design engineering unit in Japan. Employees evaluated for insomnia by the Athens Insomnia Scale (≥6 points) were divided into an intervention and control group. The intervention group received a short-term intervention (30 min) program that included sleep hygiene education and behavioral approaches (relaxation training, stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
(33 reference statements)
1
29
0
4
Order By: Relevance
“…Simeit et al found that the combined use of sleep hygiene education, relaxation techniques and cognitive and behavioural therapies in cancer patients who had insomnia increased their sleep quality (Simeit, Deck, & Conta‐Marx, ). Studies of different sample groups experiencing insomnia and fatigue in the literature have shown that sleep hygiene education alone is not sufficient, and that a combination of cognitive and behavioural therapies with relaxation techniques was found to increase sleep quality and decrease fatigue (Garland et al, ; Kaku et al, ).In this study, sleep hygiene education and relaxation techniques were used together to overcome the symptoms of insomnia and fatigue in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Simeit et al found that the combined use of sleep hygiene education, relaxation techniques and cognitive and behavioural therapies in cancer patients who had insomnia increased their sleep quality (Simeit, Deck, & Conta‐Marx, ). Studies of different sample groups experiencing insomnia and fatigue in the literature have shown that sleep hygiene education alone is not sufficient, and that a combination of cognitive and behavioural therapies with relaxation techniques was found to increase sleep quality and decrease fatigue (Garland et al, ; Kaku et al, ).In this study, sleep hygiene education and relaxation techniques were used together to overcome the symptoms of insomnia and fatigue in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using progressive relaxation exercises to reduce insomnia symptoms have found that the individuals who do the progressive relaxation exercises have better sleep quality than those who do not (Dayapoğlu, 2012;Demiralp et al, 2009;Hou, Hu, Liang, & Mo, 2014;Sun et al, 2013;Yang, Li, Hong, & Kao, 2009;Yung et al, 2004). Studies conducted with different groups reported that implementing sleep hygiene education and progressive relaxation exercises can improve insomnia (Hsu, Tsao, & Lin, 2015;Johnson & Roberson, 2013;Kaku et al, 2012). In a randomized study, Hsu et al (2015) assessed the effect of sleep hygiene education and progressive relaxation exercises on women during the period of menopause and found that sleep hygiene education and progressive relaxation exercises significantly increased subjective sleep quality and sleep duration in the experimental group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the module content, sleep health education alone was not effective to improve sleep quality significantly Carter et al, 2013). The combined sleep health education and behavioural approaches had demonstrated better results among participants, even for the non-clinical population (Ridge, Wells, Denny, Cunningham & Chalder, 2011;Kaku et al, 2012;Nishinoue et al, 2012;Carter et al, 2013;Gavrilă-Ardelean & Moldovan, 2014). Thus, the combined approach has been adopted in the study protocol to improve the intervention's effectiveness.…”
Section: Ijphcsmentioning
confidence: 99%
“…Neglect of sleep quality due to work or maladaptive sleep hygiene practice may predispose HCW to various adverse health outcomes (Peach et al, 2016;Nakada, Sugimoto, Kadotani & Yamada, 2018). While the use of medications may be helpful as a short term measure, the nonpharmacological methods would be ideal for a long term solution to promote better sleep quality Kaku et al, 2012;Morimoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%